LEARNERS’ DIFFICULTIES & STRATEGIES IN LISTENING COMPREHENSION - Saraswaty, Dwi Rara (Universitas Muhammadiyah Palembang, 2018)
Listening plays a vital role in daily lives. Everyday people listen for different purposes such as entertainmnet, academic purposes or obtaining necessary information. It is essential for learning languages since they enable to acquire insights and information, and to achieve success in communicating with others. But many students fail to seize them because of some learning difficulties in listening class. Teachers should be aware of students’ learning difficulties. Understanding students’ learning difficulties may enable EFL teachers to help students develop effective learning strategies and ultimately improve their English listening abilities. This paper focuses on how teachers enhance their positive attitude; trainthem to be responsive by giving the suitable strategies that will enable them to develop their listening skills.